Performance of Geosynthetic-Reinforced Soils Under Static and Cyclic Loading - Touahmia, M. (Engineering, Technology & Applied Science Research, 2017)
This paper investigates and discusses the composite behavior of geosynthetic reinforced soil mass. It presents the results of a series of large-scale laboratory tests supported by analytical methods to examine the performance of geogrid reinforcement subjected to static and cyclic pullout loading. The testing equipment and procedures used for this investigation are outlined. The results show that geosynthetic reinforcement can mobilize great resistance to static pulling load under high confining pressures. The reinforcement exhibits gradual deformation under cyclic loading showing no sign of imminent pullout failure for all levels of applied loads. In general, the results demonstrate that geosynthetic can be used in situations where loads are non-static, although care will be required in ensuring that appropriate factors of safety are applied to control the resulting deformation. A simplified analytical model for calculating the pulling capacity of geosynthetic reinforcement is proposed.